Evaluasi dan Implementasi Desain Universal di Universitas Tanjungpura untuk Menuju Kampus Inklusi - M. Nurhamsyah; M. Ridha Alhamdani; Syaiful Muazir; Mustikawati; Eri Putri Maharani Apriliano Puji (Arsir: Jurnal Arsitektur, 2026)
Universal design is an environmental design approach aimed at creating spaces that can be used equally by all individuals. This concept serves as an essential foundation for developing an inclusive campus that is welcoming to all members of the academic community, including persons with disabilities and individuals with limited mobility. This study aims to evaluate the existing conditions of facilities at Tanjungpura University based on the principles of universal design and to formulate a schematic concept for its implementation toward an inclusive campus. The method employed is the Post-Occupancy Evaluation (POE) with an investigative model, combined with an architectural design approach grounded in universal design principles. Data were collected through field observations and evaluations of technical, functional, and user-behavioral aspects. The analysis resulted in an evaluation matrix that serves as the basis for developing a schematic design concept applying universal design principles to campus spaces and facilities. This research is expected to serve as a reference for developing an inclusive, safe, and comfortable campus environment while contributing to the advancement of architectural knowledge through publication in nationally accredited scientific journals.